TECHNICAL MEDIA (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article discusses the analysis of Russian-language media. A huge role in preserving the norms of written speech is played by the media - television (to a lesser extent), the Internet, newspapers, magazines, books, and nowadays advertising has also joined in. For the mass reader, the media remain an example of the use of written language standards, however, spelling and stylistic errors are increasingly being made, which are especially dangerous in advertising, since they are learned by heart through repeated repetition.